P32 Targeting accuracy of the neuromate robot in DBS implantation for paediatric dystonia. Issue 3 (14th February 2019) - Ellenbogen, JR; Narbad, V; Hasegawa, H; Selway, R
Abstract : Objectives: To quantify the accuracy of DBS electrode implantation for movement disorder in paediatric patients utilising the neuroinspire™ software and neuromate® robot. Design: Retrospective, single-centre, cohort study. Subjects: Fifteen patients with dystonia (67% female; median age 11 years, range 8–18 years) underwent intervention since May 2017. Methods: DBS procedures were planned on the neuroinspire™ software and electrodes were implanted using the Renishaw neuromate® robot and Renishaw guide tubes and secured with a dog-bone plate under general anaesthetic. Post-operative CT imaging with the intra-operative O-arm was fused to pre-operative imaging. Planned entry and target coordinates were compared to actual entry and final target coordinates in order to obtain absolute and directional errors in x (medial-lateral), y (anterior-posterior) and z (dorsal-ventral) planes. Euclidean error was calculated for each electrode. Wilcoxon signed-rank test was used to analyse error. Results: Bilateral GPi were targeted and Medtronic DBS systems were implanted for each patient (n=30). Overall median Euclidean error for electrode implantation was 2.13 mm (range, 0.71–4.85; p<0.001). No discrepancy between left- and right-sided electrodes was seen (p=0.346). Absolute errors in x (med 1.25 mm, range 0.10–4.10), y (med 0.80 mm, range 0–2.70) and z (med 1.45 mm, range 0–3.90) planes were individually significant (p<0.001). On overall anterior displacement of leads was observed (med 0.55+0.85 mm, p=0.001) but there was no significant directional bias in x (p=0.219) or z (p=0.077) planes. Conclusions: We observed an improvement in the discrepancy seen between planned and actual lead location compared to a previously reported series using the Leksell frame in a similar cohort. Addressing possible compounding factors such as drilling techniques and electrode fixation should increase accuracy further. The neuromate® Robot is a reliable and accurate alternative to the Leksell frame.